Peran Kepemimpinan Transformasional Dalam Pengembangan Organisasi IPNU-IPPNU Di Desa Plumbungan Kecamatan Sukodono Kabupaten Sidoarjo - Safira Khoirotunnisa; Wahyu Eko Pujianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research analyzes the role of transformational leadership in the development of the IPNU-IPPNU organization in Plumbungan Village. Through interviews with organizational leaders, it was revealed that transformational leadership is realized through mutual learning incentives and the placement of members according to their talents. With 40 members divided into 16 men and 24 women, the organization focuses on developing individual potential. Transformational leadership not only motivates members to play an active role in organizational development at the village level, but also involves them in various programs such as cheerful camping, regular jam'iyah, and compensation for orphans. The history of the development of IPNU-IPPNU in Plumbungan Village records the concrete contribution of transformational policies in these activities, creating a positive impact on organizational spirit. Even though faced with challenges and obstacles, transformational leadership helps overcome these problems through joint deliberation. Future hopes for the development of this organization include the goal of producing young cadres with ahlussunah waljamaah character, and transformational leadership is expected to remain the main pillar in realizing development plans, continuing to encourage a spirit of collaboration and commitment to the organization's vision.